Ion Kappa Distribution Parameters in the Magnetosphere of the Earth at Geocentric Distances Smaller Than 20 Re During Quiet Geomagnetic Conditions - Espinoza-Romo, C; Stepanova, M; Eyelade, V (John Wiley and Sons Inc, 2021)
The Earth s magnetosphere is mainly a collisionless plasma system with non-Maxwellian particle distributions, which are often fitted by the kappa function. While the Maxwell distribution function is described by two parameters (density and temperature), the kappa distribution function has three parameters: density, core energy, and the kappa index that characterizes the slope at high energies. In this study, we fitted an ion flux measured by the five Time History of Events and Macroscale Interactions during Substorms satellites in the Earth s magnetosphere during quiet geomagnetic conditions by a single kappa distribution function. The data were constrained to the following regions: from seven Earth Radii (7 (Formula presented.)) to the Earth s magnetopause at the dayside, and up to 20 (Formula presented.) for other magnetic local time sectors. The two-dimensional spatial distribution of the fitted parameters and their radial dependencies were analyzed. Regions of high and low (Formula presented.) -parameter are selected and their formation is discussed. © 2021. American Geophysical Union. All Rights Reserved.